The relationship of the representative of the Levant, Nakz Al- Husami, with the Mamluk Sultan Al-Nasir Muhammad bin Qalawun (712- 740 AH/ 1312- 1339/1340 AD) - Al-Amlah, AbdulJabbar Ahmed (Arab Journal for Sciences and Research Publishing, 2022)
This research deals with the relationship of Prince Tunkaz Al- Hussami with Sultan Al- Nasir Muhammad bin Qalawun. As a result, this relationship was greatly strengthened when Al- Nasser married one of the daughters of Prince Tankaz, so visits were repeated. To the Sultan in Cairo, and in return, the Sultan’s visits to Damascus were repeated, and it came to the point that the Sultan offered the prince to marry his daughters to the children of the illiterate. In the end, they paid Nasir to get rid of Prince Tenkaz and kill him. This tragic end to the personality of Prince Tankz raises many questions and controversy about the problem of the relationship that developed between the Prince and the Sultan and ended in this tragic way. Al- Khaznadar, and this participation was in the period that preceded his rule of Damascus, and his role in the jihad against the Armenians (Maltaia and Sis) in His tenure over Damascus, especially his famous military campaign against Malatya in 715 AH/ 1315 AD, and the participation of the Damascene forces in the campaign against Sis in 737 AH/ 1337 AD.This exciting relationship, and this sad end of that relationship, is but a microcosm of the nature of the relationships that existed between the sultans themselves, the sultans and the princes, and the princes among themselves, that relationship that was based on suspicion and mistrust among them, and it often led to One side was killed.
Keywords: Tnkz Al-Hussami; Al-Nasir Muhammad